2018
DOI: 10.1016/j.virol.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Dual Insect specific virus infection limits Arbovirus replication in Aedes mosquito cells

Abstract: Aedes mosquitoes are vectors for many pathogenic viruses. Cell culture systems facilitate the investigation of virus growth in the mosquito vector. We found Zika virus (ZIKV) growth to be consistent in A. albopictus cells but hypervariable in A. aegypti cell lines. As a potential explanation of this variability, we tested the hypothesis that our cells harbored opportunistic viruses. We screened Aedes cell lines for the presence of insect specific viruses (ISVs), Cell-fusing agent virus (CFAV) and Phasi charoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 51 publications
5
85
0
Order By: Relevance
“…A previous study explored the effect of PCLPV together with Cell-fusing agent virus (CFAV) on the replication of arboviruses in cell line Aa23 derived from Ae. albopictus [63]. The Aa23 cell lines persistently infected with CFAV was further inoculated with PCLPV.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study explored the effect of PCLPV together with Cell-fusing agent virus (CFAV) on the replication of arboviruses in cell line Aa23 derived from Ae. albopictus [63]. The Aa23 cell lines persistently infected with CFAV was further inoculated with PCLPV.…”
Section: Discussionmentioning
confidence: 99%
“…Since severe disease from DENV infections can manifest as dengue 4 hemorrhagic fever/dengue shock syndrome [1], DENV establishment in the continental United 5 States is a major concern for public health agencies. In the USA, Florida has experienced 6 increases in local DENV transmission since 2009 [3], driven in part by human and pathogen 7 movement. Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Autochthonous 9 DENV infection occurs sporadically, primarily in Southern Florida with limited local cases 10 elsewhere in the state [3]. 12 13 Recently, reports have indicated that certain insect-specific viruses (ISVs) can negatively 14 impact or enhance arbovirus (including DENV) infections in insect cells [5,6] and mosquitoes 15 [7], respectively. 12 13 Recently, reports have indicated that certain insect-specific viruses (ISVs) can negatively 14 impact or enhance arbovirus (including DENV) infections in insect cells [5,6] and mosquitoes 15 [7], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We identified relatives of Phasi Charoen-like virus (PCLV) in Anopheles from Senegal and Cambodia. PCLV relatives also infect Aedes , where they were observed to reduce the replication of ZIKV and DENV arboviruses [30]. Palm Creek virus, an insect specific flavivirus, causes reduced replication of the West Nile virus and Murray Valley encephalitis arboviruses in Aedes cells [31].…”
Section: Discussionmentioning
confidence: 99%